2.5 V High‐Performance Aqueous and Semi‐Solid‐State Symmetric Supercapacitors Enabled by 3 m Sulfolane‐Saturated Aqueous Electrolytes. Issue 6 (2nd May 2022) - Cheng, Xiaolin; Yuan, Jingchao; Hu, Jiaqi; Chen, Shuangqiang; Yan, Hao; Yang, Weijing; Li, Wenrong; Dai, Yang
Abstract : Aqueous electrolytes show the potential of application for high‐performance supercapacitors. However, their limited operating voltages set limits for widespread applications. Herein, the feasibility of applying the sulfolane (SL)‐saturated 3 m LiTFSI aqueous electrolytes for supercapacitors is shown. These electrolytes possess high conductivities and wide electrochemical stable windows (ESWs), demonstrating the potential applications in high‐voltage supercapacitors. Activated carbon//3 m LiTFSI SL/Water //activated carbon supercapacitor is assembled to possess a high voltage of 2.5 V and outstanding capacitive performance (106 F g −1 at 0.5 A g −1, >10 000 cycles). Also, a high areal capacitance up to 1.52 F cm −2 is obtained by applying a high mass loading electrode (13.06 mg cm −2 ). Furthermore, a flexible symmetric semi‐solid‐state supercapacitor (2.5 V) is fabricated. Impressive performance can be obtained. Thus, the finding suggests a promising electrolyte design for high‐voltage aqueous supercapacitors. Abstract : 2.5 V‐activated carbon//3 m LiTFSI SL/Water //activated carbon supercapacitor is assembled to possess outstanding performance (106 F g −1 at 0.5 A g −1, >10 000 cycles). A high areal capacitance of 1.52 F cm −2 is obtained. Furthermore, a flexible symmetric semi‐solid‐state supercapacitor (2.5 V) is fabricated with excellent performance.